Computational prediction of CNP0387675 as a non-nucleoside inhibitor of MraY, from natural product-based multi-template screening against Pseudomonas aeruginosa - Qingxin, Zeng; Li, Dong; Guo, Aotian; Hu, Haichuan; Huang, Zhengwei; Shen, Tao (Frontiers in Microbiology, 2025)
Antimicrobial resistance driven by multidrug-resistant Gram-negative bacteria, notably Pseudomonas aeruginosa, urgently necessitates novel antibacterial targets and inhibitors. MraY, an integral membrane enzyme catalyzing lipid I formation in peptidoglycan synthesis, represents an attractive antibacterial target. In the absence of experimentally resolved structures for P. aeruginosa MraY, we developed a computational pipeline integrating multi-template homology modeling, pharmacophore-guided virtual screening, multi-template docking, molecular dynamics (MD) simulations, and medicinal chemistry profiling to identify structurally novel inhibitors. The compound CNP0387675, identified through pharmacophore-driven multi-template docking, exhibited stable binding interactions with conserved catalytic residues (ASP-195, ASP-267), validated through extensive MD simulations. Remarkably, CNP0387675 represents a non-nucleoside inhibitor, structurally distinct from traditional nucleoside-based inhibitors, thereby circumventing typical drug-likeness limitations and potential off-target toxicities associated with nucleoside analogs. Our findings underscore the potential of computationally guided, structure-based discovery strategies for novel antimicrobial scaffolds, providing critical insights and candidate inhibitors suitable for subsequent experimental validation against resistant Gram-negative pathogens.